The Development Of A Portable Fiber Optic Based Lightning Detector System - Koh, Hong Keong @ Goh Hong Keong. (2002)
This project is to demonstrate the development of a fiber optic based lightning detector system using a programmable logic controller. Basically, the project is developed to collect the lightning profiles. It is able to detect the lightning flash and store the lightning data as well as the time of occurrences into a programmable logic controller. It is capable of detecting the cloud to ground lightning, intercloud lightning, intercloud lightning and others. The data could be retrieved and viewed through the personal computer (PC) as desired. Two sections are taken into consideration for the whole system design. These sections are hardware and software design. The system hardware consists of 4 main parts. They include a sensing unit, a data transmission unit, a signal conditioning unit and a data storage unit. Most of the hardware involves circuitry designs. Based on the designs, printed circuit boards (PCBs) are constructed by using the electronics application software (PROTEL). On the other hand, the system software design is a program, which is written in ladder logic programming. The software is designed for the purpose of handling and organizing the incoming lightning data into PLC or data logger. This project was tested in 2 modes. One of the modes is the testing of the individual parts of the project. The other mode is the testing of the integration of all parts of the project, which is including software and hardware system. In individual part testing, each of the circuits was tested separately. The voltage is fed manually into the circuits for testing their performance and functionality. The software design is tested without integrating with the hardware system. In the integration testing, the hardware and the software have been combined or integrated. The project is tested and justified under the real condition of detecting lightning. Both of the testing has proven that the invention is working properly and successfully.